-8+6p=4(7+6p)

Simple and best practice solution for -8+6p=4(7+6p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8+6p=4(7+6p) equation:


-8+6p=4(7+6p)

We simplify the equation to the form, which is simple to understand
-8+6p=4(7+6p)

Reorder the terms in parentheses
-8+6p=+(+28+24p)

Remove unnecessary parentheses
-8+6p=+28+24p

We move all terms containing p to the left and all other terms to the right.
+6p-24p=+28+8

We simplify left and right side of the equation.
-18p=+36

We divide both sides of the equation by -18 to get p.
p=-2

See similar equations:

| k/100=0.15 | | 9+9n=-162 | | -(7b+7)=-14 | | k/20=0.15 | | k/8=6 | | 8x+12=11X | | g/2=16 | | -22-7n=-6+3(1-2n) | | -6y+9+4y=13 | | 8f=24 | | -3(1x+4)=-4x | | 4a^2+9a+1=0 | | x^2+3x+2=7 | | 5=-7y | | 4y-2=90 | | n^2+8=15n | | -3(8x+2)+3x=7-8x | | (3x-21)(x+1)=0 | | -60z^5+55z^4+25z^3=0 | | 4x-25=3x+18 | | -20=-2(v+3) | | (3x-3)(x+7)=0 | | 60z^5+55z^4+25z^3=0 | | p+0.13=53.11 | | 16-(2.1+4.5)0.2= | | -6(v-6)=78 | | u=18v | | 3n-p=6m | | t^2+t-20=0 | | p-0.13=53.11 | | 6*6=c | | 5d+2d+4d+1d=72 |

Equations solver categories